The Role of Vitamin C in Cancer Prevention and Therapy: A Literature Review - Marcelo Villagran; Jorge Ferreira; Miquel Martorell; Lorena Mardones (MDPI AG, 2021)
Vitamin C is a water-soluble antioxidant associated with the prevention of the common cold and is also a cofactor of hydrolases that participate in the synthesis of collagen and catecholamines, and in the regulation of gene expression. In cancer, vitamin C is associated with prevention, progression, and treatment, due to its general properties or its role as a pro-oxidant at high concentration. This review explores the role of vitamin C in cancer clinical trials and the aspects to consider in future studies, such as plasmatic vitamin C and metabolite excretion recording, and metabolism and transport of vitamin C into cancer cells. The reviewed studies show that vitamin C intake from natural sources can prevent the development of pulmonary and breast cancer, and that vitamin C synergizes with gemcitabine and erlotinib in pancreatic cancer. In vitro assays reveal that vitamin C synergizes with DNA-methyl transferase inhibitors. However, vitamin C was not associated with cancer prevention in a Mendelian randomized study. In conclusion, the role of vitamin C in the prevention and treatment of cancer is still an ongoing area of research. It is necessary that new phase II and III clinical trials be performed to collect stronger evidence of the therapeutic role of vitamin C in cancer.